2007
DOI: 10.1002/ajmg.a.31846
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between Rh status, Rh immune globulin in pregnancy and autism

Abstract: Though causes of autism are considered largely genetic, considerable concern remains that exposure to Rh immune globulin (RhIg), which until 2001 in the United States contained the preservative thimerosal, can cause autism. To determine whether mothers of children with autism are more likely to be Rh negative (Rh−) or to have received RhIg preserved with thimerosal, which is 49.6% ethyl mercury, we surveyed families of children with an autism spectrum disorder (ASD) ascertained through a University‐based autis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…The relationship between exposure to Rh immune globulin, which contained the preservative thimerosal until 2001 in the United States, and autism has also been investigated; however, no significant association has been revealed between exposure of antepartum RhIg preserved with thimerosal and an increase in risk of autistic disorder. The latter findings are in accordance with the consensus that exposure to ethymercury in thimerosal is not the cause of increased prevalence of autism [118].…”
Section: Environmental Risk Factorssupporting
confidence: 92%
“…The relationship between exposure to Rh immune globulin, which contained the preservative thimerosal until 2001 in the United States, and autism has also been investigated; however, no significant association has been revealed between exposure of antepartum RhIg preserved with thimerosal and an increase in risk of autistic disorder. The latter findings are in accordance with the consensus that exposure to ethymercury in thimerosal is not the cause of increased prevalence of autism [118].…”
Section: Environmental Risk Factorssupporting
confidence: 92%
“…However, Johnson & Johnson, a manufacturer of RhoGAM, approached Judith Miles at the University of Missouri with a significant grant to help defend the company from litigation (Evaluate™ 2012 ; Osterweil 2007 ; Wikipedia 2017 ). The industry-sponsored study by Miles and T. Nicole Takahashi ( 2007 ) commenced and concluded that exposure to ethylmercury (or Thimerosal) from RhoGAM was not associated with ASD (Miles and Takahashi 2007 ).…”
Section: Conflicts Of Interest In Mercury Exposure and Autism Researcmentioning
confidence: 99%
“…In one of these studies, Hviid and colleagues 16 found that the prevalence of autism in Denmark increased from 1991 through 1996 despite the exclusion of thimerosal in routine childhood vaccines. Epidemiologic data [31][32][33] published after the IOM Immunization Safety Committee report also fail to support a causal relationship between thimerosal exposure and autism. Fombonne and colleagues 32 recently calculated the prevalence of pervasive developmental disorders in more than 27 000 students in the greater Montreal area of Quebec, Canada, born from 1987 through 1998.…”
Section: Commentmentioning
confidence: 99%
“…Although vaccinations have been the primary source of exposure to thimerosal in childhood, a small proportion of young children during the study period would have had additional thimerosal exposure in utero through maternal immunization during pregnancy with vaccines or Rh o (D) immune globulin. 33 Similarly, sources of methylmercury exposure such as fish or human milk could not be evaluated.…”
Section: Commentmentioning
confidence: 99%